Analysis of Thermal Environment and Its Influencing Factors in Deep Stope of Metal Mine. (3rd June 2022) - You, Shuang; Sun, Jincui; Ji, Hongguang; Feng, Qixing
Abstract : In order to scientifically evaluate the thermal environment of the deep stope and its influencing factors, research was conducted on the thermal environment in Sanshandao Gold Mine, the theoretical calculations and structural analysis of heat release from 8 types of heat sources in the three sub-levels of -930 m, -945 m, and -960 m were carried out, and quantitative characterization was made on the influential degree of comprehensive heat release on the thermal environment, and it was clear that the heat release from the surrounding rock and mechanical and electrical equipment were the main parts at the deep mining site and the proportion of heat release from other heat sources is basically stable. Then, through the analysis of the influence factors of heat sources in the mining site, 17 evaluation indexes of the influence factors of the mining site thermal environment were sorted out, and the indexes' weight was calculated based on the entropy weighting method, and it was learned that the largest weight of the influence on the thermal environment factors in a single excavation working face was the water gushing in the roadway. The TOPSIS method was used to comprehensively analyze and rank the thermal damage degree in the three middle sections. The results show that the degree of thermal damage in the -960 m is more severe than that in the -930 m and -945 m. This will provide some basic basis for the evaluation and prevention of thermal damage in deep mining projects, and is of great significance for improving mine production efficiency.